Perspectives of job training in Colombia focused on the tourism sector (Revista de Investigaciones Universidad del Quindío, 2015)
Tourism sector represents for Latin American countries both a growth opportunity and an economic and social development. Nevertheless, scholarly research and skilled personnel training in this sector are still limited (Castillo et al., 2011). The aim of this study is to identify and analyze tourism academic programs which are offered in Colombia. The methodology focuses on secondary sources such as the higher education information system "SNIES", led by the Ministry of National Education "MEN" in Colombia, and the websites of the Colombian higher education institutions which offer these tourism programs. Finally, the results reveal that tourism are offered more in undergraduate programs than in postgraduate ones.
Keywords: tourism; job training; higher education; tourism competitiveness.